Posterior malleolar fractures. New classification and treatment algorithm - Yearson, Diego; Melendez, Ignacio; Anain, Federico; Siniscalchi, Santiago; Drago, Juan (Journal of the Foot & Ankle, 2020)
Objective: This study proposes a new classification of posterolateral malleolar fractures and a treatment algorithm. Methods: We divided the posterolateral malleolus, which we considered as the posterior malleolus, from the posteromedial one, which we considered as being part of the medial malleolus fracture. The experience with 77 patients treated from February 2017 to February 2020 was assessed. All of them were assessed by frontal and profile radiographies and computed tomography (CT). Among the parameters to classify these fractures, we believe the most determining ones are fracture size, followed by presence of fracture displacement. Results: Fractures were divided into those whose posterior fragment was 25% smaller than the tibial joint surface and those that compromised more than 25% of this joint. The first group underwent syndesmotic opening and was subclassified into 1A (stable fractures), which do not require surgical treatment, and 1B (unstable), which require syndesmotic stabilization. The second group, which comprised the larger fractures, was subclassified into 2 A (non-displaced fractures, or with a displacement below 2 mm), which underwent percutaneous osteosynthesis, 2B (displaced fractures), and 2C (comminuted fractures), which underwent open reduction and internal fixation using a posterior approach. Conclusion: The classifications published so far are anatomic or descriptive, but none of them proposes a therapeutic algorithm for each type of fracture. We believe it will be helpful for its interpretation and decision-making on the need to perform a posterior approach, prioritizing the anatomical reduction of the joint fragment and resolution of syndesmotic instability linked to each fracture pattern using the most simple and effective method. Level of Evidence IV; Therapeutic Studies; Case Series.